2009
DOI: 10.1021/cg800845h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of SiC/SiO2 Nanochain Heterojunctions by Microwave Method

Abstract: SiC/SiO 2 one-dimensional nanochains and SiC/SiO 2 two-dimensional X-junction and Y-junction nanochains were synthesized by using a simple and low-cost microwave method. Structural, morphological, and elemental analysis revealed that the SiC/SiO 2 nanochains consisted of 3C-SiC strings with diameters of 20-80 nm and periodic SiO 2 beads with diameters of 100-400 nm. Spectral analysis indicated that both SiC strings and SiO 2 beads produced significant photoluminescence, and the presence of SiO 2 beads enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…Compared with the previously reported luminescence from the aligned SiC NWs, the emission peak is obviously shifted [37]. Similar emission peaks at about 390 nm were also reported for the SiC/SiO 2 nanochain heterojunctions, which was attributed to the neutral oxygen vacancy formed at the interface boundary of SiC/SiO 2 [26]. In the present work, the SiC nanochains were uniformly wrapped by a thin SiO 2 amorphous film.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Compared with the previously reported luminescence from the aligned SiC NWs, the emission peak is obviously shifted [37]. Similar emission peaks at about 390 nm were also reported for the SiC/SiO 2 nanochain heterojunctions, which was attributed to the neutral oxygen vacancy formed at the interface boundary of SiC/SiO 2 [26]. In the present work, the SiC nanochains were uniformly wrapped by a thin SiO 2 amorphous film.…”
Section: Resultssupporting
confidence: 82%
“…Wei et al [26]. have synthesized 1D SiC/SiO 2 nanochain heterojunctions are composed of 3C-SiC strings and SiO 2 beads via microwave method; however, the chained homogeneous nanostructure of single-crystalline SiC has not been reported erenow.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Si nanochains can exhibit the Coulomb blockade and single‐electron transporting operation as a Si nanochain can be regarded as a serial small tunnel junction . Wei reported that the optical properties of SiC nanowires can be tailored by decorated SiO 2 beads, and presence of SiO 2 beads could enhance the photoluminescence from SiC strings …”
Section: Introductionmentioning
confidence: 99%
“…Wei et al . have synthesized 1D SiC/SiO 2 nanochains heterostructure via microwave method, which is composed of 3C‐SiC strings and SiO 2 beads . SiC/SiO 2 nanochains have also been synthesized in Li's work, via a template/catalyst‐free chemical vapor reaction approach using Si‐SiO 2 mixture powder and CH 4 as raw materials at 1250°C–1200°C .…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al 12 prepared ultra long SiC nanowires by pyrolysis of hexamethyldisilane. Qin et al 13 synthesized SiC/SiO 2 one-dimensional * Author to whom correspondence should be addressed. nanochains and SiC/SiO 2 two-dimensional X-junction and Y -junction nanochains by using a microwave method.…”
Section: Introductionmentioning
confidence: 99%